Use of Geographic Information Systems in the Cataloguing of Tourist Facilities: The Proposal of a New Research Procedure - Lukasz QUIRINI-POPLAWSKI; Marcin SEMCZUK (Communications of International Proceedings, 2021)
The purpose of the paper is to show the results of a modeling approach utilizing GIS techniques in the cataloguing of tourist facilities in selected tourist regions. Gaps in databases characterizing developed areas represent a challenge to researchers when they utilize publicly available sources such as OpenStreetMap that contain incomplete information on buildings. The studied area, the Carpathian Mountains in Ukraine, is characterized by sources that provide incomplete spatial information. This is not the case with other tourist areas across Europe. The paper discusses a novel research method that enables the determination of the number, location, and function of buildings utilizing the commercially available Collector application for ArcGIS produced by ESRI. It describes the various stages of facility cataloguing starting with preparation of input data and ending with a complete database. In the paper it is arged that GIS techniques help to make more effective management desiciees related to toutrism infrafrructure. In addition, it shows the benefits and limitations associated with the use of the herein proposed GIS application and identifies future GIS-based research directions.
Keywords: Geographic Information Systems; facility cataloguing; tourist regions; Carpathians; Ukraine; Collector for ArcGIS